ADHD in children and adolescents: Review of current practice of non-pharmacological and behavioural management - Michael O Ogundele; Hani F Ayyash (AIMS Press, 2023)
Attention deficit Hyperactivity Disorder (ADHD) is the commonest childhood neurodevelopmental disorder, affecting 3 to 9% by school age, and often persists into adulthood. ADHD in children and young people (CYP) has wide ranging multi-modal impacts on the affected CYP, their carers and the society. Co-morbidity with other neurodevelopmental, behavioural and emotional disorders is the rule rather than exception. Pharmacological treatment is not recommended as the sole therapeutic intervention, and several other non-pharmacological interventions have been advocated within a framework of Multi-modal strategy as the norm, to address both the core symptoms as well as the behavioural and other related difficulties. All paediatric professionals need to be familiar with the principles of different modalities of non-pharmacological or behavioural interventions for managing ADHD in CYP. Most published up-to-date evidence for behavioural interventions both for the core ADHD symptoms and other outcome measures are summarized in this article, including the peculiar problems related to their research. The most effective evidence-based strategies for controlling ADHD core symptoms are combination of stimulant medications with Behavioural therapy (BT) or Cognitive behaviour therapy (CBT), as well as group-based parental Psychoeducation. Standalone BT, CBT, Mindfulness, Neurocognitive training and Neurofeedback cannot currently be recommended for controlling core symptoms due to limited evidence. Other Behavioural interventions could lead to improvements in ADHD-related outcomes, including parenting skills, CYP's social skills, academic performance and disruptive behaviours. School-based non-pharmacological interventions have been shown to reduce disruptive behaviours. Executive skills are also significantly improved with use of computer-based Neurocognitive training and regular physical Cardio exercises. It is disappointing that combinations of different types of psychosocial interventions have low efficacy on both the core ADHD symptoms and other related outcomes. The readers are welcome to test their knowledge and learning efficacy through an accompanying quiz.